قرآن فہمی میں مولانا محمد شہاب الدین ندوی کا منہج و اسلوب: Review of Maulana Muhammad Shahab-ud-Din Nadvi's Quranic understanding and methodology about Quranic Thought - Rehana Imtiaz (MEI, 2023)
Mulana Muhammad Shahabud Din Nadvi is such a remarkable 20th century personality of the Islamic world who published more than a hundred books as well as more than two dozen articles on different topics related to Islamic Sharia and Islamic Thought & Philosophy .Mulana presented scientific arguments to depict supremacy and pragmatism of Islamic Shariah by describing not only unique aspects of its eternal and universal appeal but also provided research based answers to refute some objections and doubts about it.Mulana termed Islamic Shariah as a miracle and declared it to be an intellectual challenge.He declared Islamic Shariah a kind of a law which provides guidance for the welfare of the entire humanity,no other law of the world can make such a claim as Islamic Shariah does.Mulana presented Islamic Shariah as a miracle with the help of Quranic verses and highlighted its features of being logical ,moderate and full of wisdom in nature.He presented intellectual arguments to highlight that these laws are not only based on absolute intellectual foundations but are also pragmatic and logical in nature .He depicted Islamic Shariah and jurisprudence as perfect,superior and eternal and discussed the same in the light of modern age.Mulana discussed sharia issues through arguments and not by worshipping some personalities. He discussed the nature of Islamic Shariah ,its eternal principles ,some distinctive features, reality and nature of consensus and its relevance in the modern age as well as its conditions in the light of the Quranic verses and modern times. He presents Islamic Shariah as ‘unalterable ‘ in a very argumentative and logical way with historical examples .He differentiates between Islamic and human laws very beautifully .While discussing jurisprudence issues,Mulana described positive appeal of Islamic Shariah laws in the west.He particularly utilized interpretations of ‘Aljamih ul Ahkam ul Quran’and ‘Tafseer Kabeer’ in describing principles and problems of jurisprudence in the light of sayings of jurisprudence scholars,school of thought in jurisprudence and their deductive methodology .He adopted deductive methodology in describing principles and problems of jurisprudence .Mulana presented supremacy and superiority of Islamic Shariah as well as its pragmatism ,wisdom and unalterable nature with intellectual arguments in the perspective of modern age.